COMPARATIVE STUDY OF SAFETY FACTOR AND STRENGTH FACTOR IN NUMERICAL MODELING OF PILLAR STABILITY CASE USING HOEK & BROWN FAILURE CRITERION - Hardiono, Enver
In underground mining operations, supports are essential to prevent the collapse of mine openings and ensure successful mining activities. One such support structure is the pillar. To evaluate the safety of these pillars, calculations are performed to determine their strength and the magnitude and direction of the stresses they experience. A commonly used metric to assess the safety of a pillar design is the Factor of Safety. This final study to investigate the relationship between Strength Factor and Factor of Safety for underground mine pillars with varying width-to-height ratios. Additionally, it explores whether Strength Factor can adequately represent the safety factor under these conditions. The analysis conducted in this study revealed that both Strength Factor and Factor of Safety values exhibit a similar trend, increasing alongside the increasing width-to-height ratio. However, Strength Factor values generally tend to be higher than Factor of Safety values due to the difference in the comparisons employed in the calculations, which can lead to an overestimation of pillar safety.